Effectiveness of behaviour change techniques on lifestyle interventions of patients with a high risk of developing cardiovascular disease. Using a qualitative approach. (21st January 2020) - Kuriakose, Lisa; Kuczynska, Paulina; Timpel, Patrick; Yakub, Farah; Bayley, Adam; Papachristou Nadal, Iliatha
Abstract: This study aimed to identify key active ingredients on the maintenance of behaviour change for lifestyle interventions of patients with a high risk of developing cardiovascular disease (CVD) who participated in a MOtiVational intErviewing InTervention (MOVE IT) randomised control trial (RCT). A process evaluation was carried out using focus groups. Twenty‐six participants of the MOVE IT RCT were purposively recruited and split into six focus groups. Four groups had attended six or more sessions of the intensive phase (completers) and two groups had withdrawn before the end of the intensive phase or had not attended any sessions (non‐completers). Focus groups were audio recorded, transcribed verbatim and analysed inductively using thematic analysis. Three overall themes were generated from the six focus groups: (a) long‐term benefits from diet and physical activity education, (b) group versus individual structure and adherence and (c) impact on health beliefs and risk of CVD. A fourth theme was generated from the two groups of non‐completers only: (d) need for professional rapport building and feedback. We found that the key active ingredients for effective behavioural change in lifestyle interventions are having well‐developed rapport between facilitators and patients; and providing alternative forms of feedback to encourage maintenance of behaviour change. Furthermore, such programmes also need to have established and strong relationships with associated health professionals (i.e. the General Practitioner) to increase participation and maintenance of engagement.